(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Juvenile delinquency, or the involvement of minors in criminal behavior, is a pressing social issue that poses challenges to communities worldwide. This study aims to assess the escalating number of juvenile delinquents in Barangay Bignay, Valenzuela City. The findings revealed the several risk factors contributing to the problem, including the family environment of the child, peer pressure, and poverty; the problems encountered by the respondents in handling juvenile delinquents are the uncooperative parents. Additionally, the research highlighted the role of the community and its stakeholders, such as local government units, law enforcement agencies, and social service providers, in addressing the issue of juvenile delinquency. Based on the assessment, recommendations for intervention and prevention strategies were proposed, including implementing community-based programs that focus on addressing risk factors, providing opportunities for education and skills development, and strengthening family support systeMs. The study underscores the need for collaborative efforts among various stakeholders to effectively combat the rising cases of juvenile delinquency in Barangay Bignay and promote the well-being and rehabilitation of young offenders.